2018
DOI: 10.1186/s12889-018-5957-9
|View full text |Cite
|
Sign up to set email alerts
|

Voices for food: methodologies for implementing a multi-state community-based intervention in rural, high poverty communities

Abstract: BackgroundRural communities experience unique barriers to food access when compared to urban areas and food security is a public health issue in rural, high poverty communities. A multi-leveled socio-ecological intervention to develop food policy councils (FPCs), and improve food security in rural communities was created. Methods to carry out such an intervention were developed and are described.MethodsA longitudinal, matched treatment and comparison study was conducted in 24 rural, high poverty counties in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Programs that link patients to emergency food pantries and other community resources to help support unmet need for food assistance may also be helpful [ 73 ]. Lastly, supporting access to healthful foods and beverages in food environments such as federal food assistance programs and emergency food assistance network may be particularly relevant for disadvantaged subgroups to improve diet, health, and wellness [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Programs that link patients to emergency food pantries and other community resources to help support unmet need for food assistance may also be helpful [ 73 ]. Lastly, supporting access to healthful foods and beverages in food environments such as federal food assistance programs and emergency food assistance network may be particularly relevant for disadvantaged subgroups to improve diet, health, and wellness [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small-scale and localized research studies have also suggested that clients rely on food pantries for large portions of their food ( 14 , 15 ) over long periods of time ( 1 , 14 , 16 ). The persistent nature of food insecurity and the chronic food needs of clients have been identified by hunger relief agencies in their recent move away from the term “emergency food system,” prompting food pantries to adopt new policies and interventions to improve the healthfulness and client-centeredness of their services ( 4 , 14 , 17 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…While not statistically significant relative to controls, these findings hold promise for future interventions aiming to improve shopping behaviors among adolescents, a critical priority population for behavior change as adolescents are transitioning into adulthood. To facilitate healthier purchases in future studies, intervention content could use ecological momentary assessment (prompts that are capturing where the individual is shopping at the given moment [33]) techniques to send messages when adolescents are “in the moment” of purchasing food at various food venues.…”
Section: Discussionmentioning
confidence: 99%